Biomaterials based on a natural polysaccharide: alginate - Rinaudo, Marguerite (TIP Revista Especializada en Ciencias Químico-Biológicas, 2015)
In this short review, our objective was to describe few new applications of a natural polysaccharide extracted from algae, the alginates. Firstly, the chemical composition is recalled and the main techniques used for characterization are cited. The role of guluronic acid blocks (GG blocks) is particularly important for gel mechanical properties in presence of calcium counterions. Then, the main applications in food and biomedicine are briefly mentioned followed by tentative applications in packaging, paper, textil and wound dressing which are described. Especially, fine fibers are produced now industrially under mixed sodium/calcium ionic form.